Towards modern sustainable cities: Review of sustainability principles and trends. (1st August 2019) - Sodiq, Ahmed; Baloch, Ahmer A.B.; Khan, Shoukat Alim; Sezer, Nurettin; Mahmoud, Seif; Jama, Mohamoud; Abdelaal, Ali
Abstract: Human capital development, attractions of sustainable living standards and renewed concerns for the planet have redirected city planners to a new frontier: the creation of sustainable cities. This is evident in some initiatives taken to create cities with low to zero carbon emissions, build sustainable structures and create higher institutions of learning where sustainability practices are entrenched in their curricula. Examples of the forerunners of sustainable cities are abound; from the Middle East (Education City in Qatar and Masdar City in Abu Dhabi) to Far East (Dongtan Institute in China and New Songdo City in South Korea), new cities imbued with sustainability practices are springing forth. There are 400 big cities and 23 mega cities presently occupying the world urban spaces, with estimates of about one and 10 million inhabitants, respectively. Ironically cities occupy about 2% of the earth surface, they however consume 60–80% of global energy. The global urban population rose from 220 million to about 2.8 billion in the 20th century, and it is projected that by 2050, this will increase to 6.9 billion, which is about 70% of the world population. Therefore, sustainability campaigns, when directed at cities, would have intended impacts due to a number of factors associated with cities: large population, hub of intellectual and social integration, high consumption, etc. In creating modern sustainable cities however, the attention of cities' planners and policymakers alike should be on those goals that come under the banner of sustainability, especially when designing new or retrofitting existing human settlements (the cities); such as human capital development, energy conservation and energy efficiency, water security, efficient use of earth-abundant resources, transportation, building standards, social and economic equity, and food wastes management. Although there are few review articles in the literature that separately deal with individual sustainability fundamentals, there is a dearth of publication consolidating key sustainability principles required for modern cities. This paper reviewed each element needed to make a functional sustainable city. We adopted a simple approach; we explained each sustainability principle, highlighted its core values and gave reasons why it is an important candidate to be considered in making a working city. We critiqued the current sustainable cities by stating reasons for their strengths and explanations for their deficiencies. We engaged the future sustainable cities' planners to learn from the failures of some of the earlier hurriedly executed sustainable cities in order to have the most important elements of sustainability present in their future project execution.